PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN REPUTASI AUDITOR TERHADAP PENGUNGKAPAN INTERNET FINANCIAL REPORTING - Mei Anisa Ahlaqulkarima; Ceacilia Srimindarti (Jurnal Akuntansi dan Pajak, 2022)
Internet financial reporting is the delivery of company financial information via the internet on the company's website with the aim of strengthening good relations with investors, analysts, shareholders, or other users of financial statements. The purpose of this research is to examine and analyze the effect of company size, profitability, and auditor reputation on internet financial reporting disclosures in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in four consecutive periods in 2017-2020, as many as 699 companies. In this study using a sampling method, namely purposive sampling technique with several selected criteria in order to obtain a sample of 308 companies. This study uses secondary data in the form of numbers that are processed into a statistical measurement scale. Data collection techniques using documentation techniques, literature study and observation of manufacturing company websites. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that company size (SIZE), profitability (ROA) and auditor reputation (REP_AUD) have a significant positive effect on disclosure of internet financial reporting.